Quartierszenario Ostfildern Scharnhauser Park 2030. - Jessen, Johann (TH Zürich, ORL-Institut, 2005)
Beim Quartiersszenario Ostfildern Scharnhauser Park 2030 handelt es sich in vielfacher Hinsicht um einen Prototyp. Um langfristige Entwicklungsperspektiven eines Neubaugebietes zum Gegenstand aktueller lokalpolitischer Diskussionen zu machen, wurde das Quartiersszenario mit Hilfe des Einsatzes neuer Medien (digitale Panoramabilder) in seinen Schwerpunkten - demografische Entwicklung, Zuwanderung und Integration, Veränderung des Wohnens durch technische Innovationen - dargestellt und in einem "open space"-Workshop eingesetzt. Der Beitrag berichtet aus Sicht der wissenschaftlichen Begleitforschung und erörtert die Perspektiven für weitere Einsatzmöglichkeiten medienunterstützter Darstellungstechniken. oc/difu

In the last decade, new information and communication technologies have extended the means of visualizing concepts of urban planning and design immensely. Are there practical ways of using these technologies to create and illustrate urban scenarios as a tool for citizen participation? Can this be achieved at reasonable cost and thus become part of the urban planning routine someday? The article presents the results of a case study on a neighbourhood scenario for Scharnhauser Park, a new urban development (still under construction) in Ostfildern, a small town close to Stuttgart. A prototype of a neighbourhood scenario was developed on a digital basis, experimenting with collage techniques. The scenario illustrates an imaginary future for Scharnhauser Park in the year 2030. The scenario was discussed in public during an "open space" workshop with the new residents of the neighbourhood, dedicated Ostfildern citizens, and local officials. All in all, the response to this method of stimulating public discussion on future urban problems was very encouraging. difu
Keywords: Stadtplanung; Stadtentwicklungsplanung; Städtebau; Darstellung; Szenario; Stadtteilplanung; Stadtquartier; Ordnungspolitik; Regionalplanung; Öffentlichkeit; Partizipation; Neue Medien